In Memoriam Guy Lemeunier (Paris, 1942 - Murcia, 2010) - Martínez Carrión, José Miguel (Áreas: Revista Internacional de Ciencias Sociales, 2010)
In Memoriam Guy Lemeunier (Paris, 1942 - Murcia, 2010).